Special physical education : physical activity, sports, and recreation - Jansma, Paul.; French, Ron. (Englewood Cliffs, N.J. : Prentice Hall, 1994)
This book is divided into four parts: Introduction; The noncategorical approach; The categorical approach; and Special topics.
Keywords: Education; Physical education for handicapped persons